Edward Blake, Irish Nationalist : A Canadian Statesman in Irish Politics 1892-1907 - Banks, Margaret A., 1928- (Book collections on Project MUSE., 1957)
An informative account, based on careful research, of Edward Blake, an enigmatic figure in Canadian politics, whose career encountered unequalled frustrations and discouragement, but whom Sir Wilfrid Laurier unhesitatingly termed "the most powerful intellectual force in Canadian political history."